Qualidade de vida de pessoas em situação de rua do Brasil Central - Soares Neto, Alcides Pereira (2016)
The objective of this cross-sectional study was to evaluate the quality of life of individuals living in the street, homeless, from August to October 2015. Data collection was conducted through a questionnaire containing questions related to social, economic and demographic aspects and the generic quality of life instrument for World Health Organization Quality of Life - Bref (WHOQOL-Bref). To evaluate factors associated with QoL, were used multiple linear regression. The level of significance was set at ≤ 5 %. Cronbach's alpha ranged from 0,66 to 0,80, implying good instrument reliability. the study population consisted of 150 individuals, with the youngest aged 18 and the oldest 82 years. The mean scores of the WHOQOL-Bref were higher in Physical (68,1) and Psychological (66,6) domains and the lower scores were obtained from the Environment (44,1) and Social Relations domains (56,6). Significant averages in quality of life were demonstrated in association with male homeless, married, age (30 - 40 years), non-users of illicit drugs and without reported toothache and discrimination. This study allowed identifying the dimensions of life of homeless that are affected, emphasizing the need to creation of public policies and social support to effectively reduce the vulnerabilities of these individuals. It also allows us to reflect on the nurses responsibility in promoting health, and therefore, improve their quality of life of people.